Estudo da influência da adição de etanol e/ou metanol ao biodiesel associado a ferramentas quimiométricas - Anna Helena Silva Paraizo (2012)
The objective of this work is to study the influence of the addition ofalcohol methanol or ethanol - to biodiesel. Therefore, Principal Components Analysis (PCA) was combined with infrared spectra with the aim of separating soybean and tallow biodiesel samples with different alcohol contents of ethanol or methanol. PCA yielded a good reduction of data regarding the spectral interval in the range of 4.000 to 1.200 cm-1, obtaining easily interpretable and examinable graphics maintain high explained variance. In this model with merely four principal components it was possible to represent 96,94% of total variability. With the first principal component, the samples were separated into a samples with high alcohol content equal to or above 5% (v/v) and sampleswith low alcohol content equal to or below 2% (v/v). The Partial Least Squares Discriminant Analysis (PLS-DA) confirmed that the PCA separation occurred with no error percentage. The Partial Least Squares (PLS) was used to predict the alcohol content of the samples, with only three latent variables, which provided an accumulated variance of 96,08% in X and 98,85% of variance in Y. The low RMSEC and RMSEP values obtained indicate that this methodology can be employed in place of the gas chromatography technique provided by the EN 14110 and NBR 15343 norms, it is also fast. The Thermogravimetry alsoconfirmed the results of the Molecular Absorption Spectrometry in the Fourier Transformed Infrared Region (FTIR), showing that the samples with high alcohol content suffered different decomposition from the samples with low alcohol content. Furthermore, the influence of alcohol content in the biodiesel was studied for two physico-chemical properties (oxidative stability and flash point) in accordance with ASTM D 93 and EN 14112, respectively. The flash point of the samples was greatly affected by the presence of alcohol, due to high volatility of this compound. With increase of the concentration of alcohol, the flash point of the samples decreased while the oxidative stability increased